High-loading, ultrafine Ni nanoparticles dispersed on porous hollow carbon nanospheres for fast (de)hydrogenation kinetics of MgH2 - Shun Wang; Mingxia Gao; Zhihao Yao; Kaicheng Xian; Meihong Wu; Yongfeng Liu; Wenping Sun; Hongge Pan (Journal of Magnesium and Alloys, 2022)
Magnesium hydride (MgH2) is one of the most promising hydrogen storage materials for practical application due to its favorable reversibility, low cost and environmental benign; however, it suffers from high dehydrogenation temperature and slow sorption kinetics. Exploring proper catalysts with high and sustainable activity is extremely desired for substantially improving the hydrogen storage properties of MgH2. In this work, a composite catalyst with high-loading of ultrafine Ni nanoparticles (NPs) uniformly dispersed on porous hollow carbon nanospheres is developed, which shows superior catalytic activity towards the de-/hydrogenation of MgH2. With an addition of 5 wt% of the composite, which contains 90 wt% Ni NPs, the onset and peak dehydrogenation temperatures of MgH2 are lowered to 190 and 242 °C, respectively. 6.2 wt% H2 is rapidly released within 30 min at 250 °C. The amount of H2 that the dehydrogenation product can absorb at a low temperature of 150 °C in only 250 s is very close to the initial dehydrogenation value. A dehydrogenation capacity of 6.4 wt% remains after 50 cycles at a moderate cyclic regime, corresponding to a capacity retention of 94.1%. The Ni NPs are highly active, reacting with MgH2 and forming nanosized Mg2Ni/Mg2NiH4. They act as catalysts during hydrogen sorption cycling, and maintain a high dispersibility with the help of the dispersive role of the carbon substrate, leading to sustainably catalytic activity. The present work provides new insight into designing stable and highly active catalysts for promoting the (de)hydrogenation kinetics of MgH2.